2010
DOI: 10.5897/jmpr10.191
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge and sustainable development in the Tones Valley of Garhwal Himalaya

Abstract: The inhabitants of the Tones Valley have survived on their traditional management practices for their needs. The paper has looked at traditional systems of forestry and agricultural system management in the west-central Himalayan region. Based on a detailed analysis of traditional knowledge that is linked with biodiversity, natural and human-managed, various possibilities for sustainable management of natural resources, with concerns for sustainable livelihood of local communities have been explored for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Collectively they sketch a consistent pathway characterized by extreme restrictions set by external actors that are rendered unimplementable by a combination of insufficient resources, governance weaknesses, social diversity, and unequal power relations, negative social impacts, and consequent forms of local resistance (Mwakaje et al 2013, Vergara andBarton 2013). For two different cases in India, researchers found that governance weaknesses such as low accountability can lead to various forms of corruption, which, alongside the displacement of local institutions, opens the door to land and resource grabs, especially where conservation is poorly financed (Rawat et al 2010, Chhotray 2016.…”
Section: Imposed Conservation Suffers Weak Legitimacy That Can Trigger Local Resistancementioning
confidence: 99%
“…Collectively they sketch a consistent pathway characterized by extreme restrictions set by external actors that are rendered unimplementable by a combination of insufficient resources, governance weaknesses, social diversity, and unequal power relations, negative social impacts, and consequent forms of local resistance (Mwakaje et al 2013, Vergara andBarton 2013). For two different cases in India, researchers found that governance weaknesses such as low accountability can lead to various forms of corruption, which, alongside the displacement of local institutions, opens the door to land and resource grabs, especially where conservation is poorly financed (Rawat et al 2010, Chhotray 2016.…”
Section: Imposed Conservation Suffers Weak Legitimacy That Can Trigger Local Resistancementioning
confidence: 99%
“…(Fabaceae) PLP 9981Safed kathiShrubA common shrub of the Himalayan regionMiscellaneousRopes, sacs [45], tools [48]8 Hordeum vulgare L. (Poaceae) PLP 9982JooGrassSurface roughness and polarity of its fibre are of importanceArtefact-9 Indigofera heterantha Baker (Fabaceae) PLP 9983Kai kathiShrubThe wood is hard and weighs around 55 lbs per cubic footMiscellaneousTool, handles of axe, pick axe, scythe, hammer [48]10 Juglans regia L. (Juglandaceae) PLP 9959KhodTreeThe wood is light, durable and has good working qualities. Its weight is about 44 lbs per cubic footTool, miscellaneousConstruction, furniture, cabinets [43, 44]; agricultural implements, plough, yoke [46–48]. 11 Picea smithiana Boiss.…”
Section: Resultsmentioning
confidence: 99%
“…(Pinaceae) PLP 9984RaiTreeLight weight, it is easy to saw and work. Its weight is about 31lbs per cubic footTool, miscellaneous, storage structure, constructionStorage structures, boxes [47]; house construction [44]. 12 Pinus wallichiana A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations